Direct Evidence for the Polymeric Nature of Polydopamine. (18th December 2018) - Delparastan, Peyman; Malollari, Katerina G.; Lee, Haeshin; Messersmith, Phillip B.
Abstract: Inspired by the adhesive proteins of mussels, polydopamine (pDA) has emerged as one of the most widely employed materials for surface functionalization. Despite numerous attempts at characterization, little consensus has emerged regarding whether pDA is a covalent polymer or a noncovalent aggregate of low molecular weight species. Here, we employed single‐molecule force spectroscopy (SMFS) to characterize pDA films. Retraction of a pDA‐coated cantilever from an oxide surface shows the characteristic features of a polymer with contour lengths of up to 200 nm. pDA polymers are generally weakly bound to the surface through much of their contour length, with occasional "sticky" points. Our findings represent the first direct evidence for the polymeric nature of pDA and provide a foundation upon which to better understand and tailor its physicochemical properties.